Los protagonistas de la prensa (Los primeros escritores de periódicos costarricenses. 1833-1850) - Vega Jiménez, Patricia (1993)
The purpose of this article is to analyze the main writers publishing in Costa Rican newspapers during the first half of the 19th century. This is a prior step for a discussion of the development of the press and the collective transmission of ideas by means of printed material, and of their impact of 19th century society.